2014
DOI: 10.1016/j.nimb.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Geant4-DNA simulation of S-values with other Monte Carlo codes

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…For 20 keV electron the CSDA electron range in liquid water is 8.98 70.02 μm, that is, comparable to the cell diameter (10 μm). This finding is consistent with the results of Emfietzoglou et al (2007) and André et al (2014) who showed that differences between Monte Carlo and MIRD data are largest when the electron range becomes comparable to the sphere size. We should point out that, according to the MIRD database, the value of S(N'CS) for the present cell dimensions is zero for electron energies up to 5 keV.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For 20 keV electron the CSDA electron range in liquid water is 8.98 70.02 μm, that is, comparable to the cell diameter (10 μm). This finding is consistent with the results of Emfietzoglou et al (2007) and André et al (2014) who showed that differences between Monte Carlo and MIRD data are largest when the electron range becomes comparable to the sphere size. We should point out that, according to the MIRD database, the value of S(N'CS) for the present cell dimensions is zero for electron energies up to 5 keV.…”
Section: Resultssupporting
confidence: 93%
“…The S-values of single cells and cell clusters for In-111 was also studied using the MCNP code (Cai et al, 2010). André et al (2014) determined cellular S-values for I-131, I-132, I-133, I-134, I-135 and monoenergetic sources using Geant4-DNA and compared results with other Monte Carlo codes. The Geant4-DNA results were found to be in good agreement with the data obtained using other Monte Carlo codes like CELLDOSE (Champion et al, 2008) (difference up to 8%), MC4V (Emfietzoglou et al, 2008) (difference up to 4%), PENELOPE (Salvat et al, 2008) (difference up to 4%), MCNP (Cai et al, 2010) (difference up to 10%), and EGSnrc (Kawrakow, 2000) (difference up to 7%).…”
Section: Introductionmentioning
confidence: 99%
“…First attempts to calculate S-values in liquid water with Geant4-DNA are described in [109]. In this work, the authors calculated S-values for incident mono-energetic electrons (100 eV to 20 keV) and for five iodine isotopes ( 131 I to 135 I -the spectra were obtained from previous MC simulations) in simple spherical geometrical targets: spheres of varying radius (10 nm to 1 micrometre) for mono-energetic electrons uniformly distributed in the spheres, or colloid and follicular cells of the thyroid for the five iodine isotopes (two concentric spheres of liquid water separated by 10 micrometres: the inner sphere contains the radionuclide uniformly distributed and its radius varies between 15 and 250 micrometres, representing colloids, whereas the surrounding 10-micrometre thick spherical region represents follicular cells).…”
Section: S-valuesmentioning
confidence: 99%
“…The reader is invited to refer to [109] for full references on these codes. The Kolmogorov-Smirnov test was also used in this study to compare Geant4-DNA to the other Monte Carlo codes.…”
Section: S-valuesmentioning
confidence: 99%
See 1 more Smart Citation